SYNTHESIS AND CHARACTERIZATION OF IRON OXIDE NANOPARTICLES FOR INCORPORATION INTO ORGANIC ELECTRONIC DEVICES - Kunyu, Liang (My University, 2018)
Surface modification of electrodes becomes a powerful process to improve the performance of organic electronic devices such as organic light emitting diodes (OLEDs) and organic photovoltaic cells (OPVs), boosting their further commercialization. Effective improvement can be achieved by introducing several types of nanoparticles onto the electrodes. Magnetic fields also have influence in the organic electronics, due to charge transport mechanisms of organic semiconducting materials. Therefore, magnetic nanoparticles are of particular interest. Magnetic γ-Fe2O3 nanoparticles have been produced using diblock copolymer reverse micelles method. The processes were elucidated in detail by Raman spectroscopy to reveal the iron oxide evolution. Compositional and structural information of individual γ-Fe2O3 nanoparticles were also characterized thoroughly by transmission electron microscopy (TEM) equipped with energy-dispersive X-ray spectroscopy (EDX) and electron energy loss spectroscopy (EELS), while their magnetic properties of the nanoparticles arrays were also evaluated by superconducting quantum interference device (SQUID) magnetometer. The low temperature annealing process was developed to facilitate the incorporation of γ-Fe2O3 nanoparticles in practical devices. Introducing γ-Fe2O3 nanoparticles onto the anode of basic OPV devices showed a positive effect on performance during the preliminary test. By using several methods, dispersion of γ-Fe2O3 nanoparticles can be tuned, examined by disLocate which is a comprehensive suite of tools for quantitative dispersion analysis. Additionally, the size of the nanoparticles can be changed simply by changing the loading ratio of FeCl3 below the maximum loading which was determined by quantum mechanical mapping using atomic force microscopy (AFM-QNM). With high control in terms of size and dispersion, the magnetic γ-Fe2O3 nanoparticles are ready to be employed to study the surface modification and magnetic effect on organic electronic devices.
Keywords: iron oxide; nanoparticles; structure; Raman; dispersion; magnetic